2021
DOI: 10.1007/s42235-021-0034-y
|View full text |Cite
|
Sign up to set email alerts
|

Fish Lateral Line Inspired Flow Sensors and Flow-aided Control: A Review

Abstract: Any phenomenon in nature is potential to be an inspiration for us to propose new ideas. Lateral line is a typical example which has attracted more interest in recent years. With the aid of lateral line, fish is capable of acquiring fluid information around, which is of great significance for them to survive, communicate and hunt underwater. In this paper, we briefly introduce the morphology and mechanism of the lateral line first. Then we focus on the development of artificial lateral line which typically cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 96 publications
0
17
0
Order By: Relevance
“…[152,153] In recent years, researchers have made good progress through the bionic sideline system. [154][155][156][157] In addition, the integration of flexible sensing and soft actuating is also an important part of realizing intelligent control for soft robots. A series of related studies have become a hot topic of research.…”
Section: Discussionmentioning
confidence: 99%
“…[152,153] In recent years, researchers have made good progress through the bionic sideline system. [154][155][156][157] In addition, the integration of flexible sensing and soft actuating is also an important part of realizing intelligent control for soft robots. A series of related studies have become a hot topic of research.…”
Section: Discussionmentioning
confidence: 99%
“…Since the robot fish's electronic communication system frequently uses the same channel, collisions always occur during communication. To solve this problem, based on carrier sense multiple access with collision avoidance (CSMA/CA), an electronic communication system was proposed by Zhang et al [54] . This system incorporated a communication channel detection circuit and employed a CSMA/CA-based protocol.…”
Section: Communication Of Multiple Robot Fishesmentioning
confidence: 99%
“…Fish can perceive information from the surrounding fluid using the lateral line system (LLS) [55]. This has serious implications for their underwater survival.…”
Section: Communication Of Multiple Robot Fishesmentioning
confidence: 99%
“…Biomimicry studies have shown that fish can use the lateral line system to obtain information such as the underwater environment and the location of targets, which is essential for fish to move, hunt, and avoid predators [4]. The lateral line system is a type of neuron on the surface of fish that senses surface pressure to obtain underwater information [5][6][7].…”
Section: Introductionmentioning
confidence: 99%